طريقة استخدام لعبة تخمين الصور وفعاليتها لتعليم مهارة القراءة لدى تلاميذ الصف السادس في المدرسة الإبتدائية الإسلامية الراية - Robati, Kisti; Hariyanto, Hariyanto; Hasanah, Uswatun; Nuradi, Nuradi (Al-Uslub: Journal of Arabic Linguistic and Literature, 2025)
Reading is considered one of the fundamental skills through which a person understands the relationship between written symbols and spoken sounds. The ideal proficiency in reading is evident when a person can read effectively, comprehend texts, and expand their vocabulary. Through reading, a person can understand the Holy Quran, the Hadiths, and Arabic language books. One of the schools where Arabic is taught is Al-Rayah Islamic Elementary School in Sukabumi. The lack of diversity in the teacher's use of educational aids and the students' perception of the difficulty of learning Arabic indicate their reluctance to learn it. The objective of this research is to determine the method of using the picture guessing game and its effectiveness in teaching reading skills. This research is a qualitative and quantitative study using an experimental method with a one-group pretest-posttest design. The data obtained are in numerical form through observation, interviews, and tests. The data analysis method employed by the researcher is the t-test using the Excel program to determine (p(T<=t), two-tail). The research reached two conclusions: the use of the picture guessing game in teaching reading skills consists of two versions: one implemented through PowerPoint and the other using written tools. The effectiveness of using the picture guessing game was evaluated through statistical calculation in Excel. The pretest and posttest results showed a (P(T<=t), two-tail) value of 0.000778484, which is less than 0.05. This means that H0, which states that the use of the game is not effective, is rejected, and H1, which states that the use of the game is effective, is accepted.